2020
DOI: 10.1542/peds.2020-0242f
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention, Parent Talk, and Pragmatic Language in Children With Hearing Loss

Abstract: BACKGROUND AND OBJECTIVES: Pragmatic language skills form the foundation for conversational competence, whereas deficits in this area are associated with behavioral problems and low literacy skills. Children who are deaf or hard of hearing demonstrate significant delays in this critical area of language. Our purpose with this research was to identify variables associated with pragmatic language ability in children who are deaf or hard of hearing. METHODS: This was a longitudinal study of 124 children with bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 35 publications
(60 reference statements)
0
31
0
8
Order By: Relevance
“…In this study children within the target age range from 0 to 5 1 2 years are recruited across the duration of the study. Data is gathered at six child ages (9,18,27,36,48, and 66 months and at baseline (at enrolment in family centered early intervention (FCEI)). Thus, depending on the age a child enters the study, there are at least 1 and at a maximum seven measurement points for a child (i.e., a child that enters the study in the first study year at the age of nine months will ideally participate in all seven measurement points, and a 9-month-old child who enters the study in the second year will participate in six measurement points).…”
Section: Methodsmentioning
confidence: 99%
“…In this study children within the target age range from 0 to 5 1 2 years are recruited across the duration of the study. Data is gathered at six child ages (9,18,27,36,48, and 66 months and at baseline (at enrolment in family centered early intervention (FCEI)). Thus, depending on the age a child enters the study, there are at least 1 and at a maximum seven measurement points for a child (i.e., a child that enters the study in the first study year at the age of nine months will ideally participate in all seven measurement points, and a 9-month-old child who enters the study in the second year will participate in six measurement points).…”
Section: Methodsmentioning
confidence: 99%
“…Both fathers and mothers felt supported by their primary EI provider in promoting their child's language and social-emotional development; indeed, these are areas in which FCEI has been shown to be effective in a variety of studies [1,44,57,58]. Both fathers and mothers indicated that they felt supported by their primary EI provider and gained knowledge that assisted in dealing with their child being DHH in daily situations.…”
Section: Similarities Among Fathers and Mothersmentioning
confidence: 93%
“…In order to optimise social interactions and indeed impact on multiple positive life outcomes, Yoshinaga-Itano, Sedey, Mason, Wiggin, and Chung's (2020) research indicates the need to expand the 1-3-6 criteria for best practice for children with HL. The inclusion of a greater quantity of parent talk particularly within the preschool years is proposed.…”
Section: Implications For Practicementioning
confidence: 99%